Effect of long fasting on myocardial accumulation in 18F-fluorodeoxyglucose positron emission tomography after chemoradiotherapy for esophageal carcinoma. (21st December 2017) - Ishida, Yuichi; Sakanaka, Katsuyuki; Itasaka, Satoshi; Nakamoto, Yuji; Togashi, Kaori; Mizowaki, Takashi; Hiraoka, Masahiro
Abstract: This study sought to evaluate the effect of fasting time prior to 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) on myocardial accumulation of FDG in patients receiving radiotherapy for esophageal carcinoma, and the spatial relationship between the irradiated dose and myocardial accumulation of FDG. Forty-one patients with thoracic esophageal carcinoma received FDG-PET with <18-h (24 patients) or ≥18-h (17 patients) fasting status. Their myocardial accumulation patterns of FDG were categorized using the maximal standardized uptake value (SUVmax ) into three types: physiological, focal and no pathological accumulation. The incidence rates of each pattern were then compared using the Fisher's exact test between two types of fasting, ≥18-h and <18-h, prior to FDG-PET. Additionally, the left ventricle was defined using four subsites depending on the irradiated doses, and the SUVmax values were compared among the subsites using the Kruskal–Wallis test. The incidence of the physiological accumulation pattern decreased significantly more in the ≥18-h fasting status group than in the <18-h fasting group (18% versus 71%, P = 0.002), and the focal accumulation of FDG was detected at a significantly higher rate (65% versus 13%, P = 0.001). The left ventricular subsites receiving the higher doses showed significantly higher SUVmax values than did the subsites receiving the lower doses ( P < 0.001). In conclusion, radiotherapy was associated with abnormal myocardial accumulation of FDG. Long fasting for 18 h or more prior to FDG-PET would be useful in detecting subsequent myocardial damage from chemoradiotherapy compared with <18-h fasting prior to FDG-PET.